Body fluids may contribute to human-to-human transmission of severe acute respiratory syndrome coronavirus 2: evidence and practical experience - Amir Hossein Mohseni; Sedigheh Taghinezhad-S; Zhigang Xu; Xiangsheng Fu (BMC, 2020)
Abstract Background In December 2019, an unbelievable outbreak of pneumonia associated with coronavirus was reported in the city of Wuhan, Hubei Province. This virus was called severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Although much effort has been spent on clarifying the transmission route of SARS-CoV-2, but, very little evidence is available regarding the relationship between human body fluids and transmission of SARS-CoV-2 virus. Considerable evidence from hospital in Wuhan indicates that strict rules to avoid occupational exposure to patients' body fluids in healthcare settings, particularly among every medical staff, limited person-to-person transmission of nosocomial infections by direct or indirect contact. Conclusion We tried to provide important information for understanding the possible transmission routes of SARS-CoV-2 via body fluids including bronchoalveolar-lavage, saliva, blood, urine, feces, sputum, tears, and semen in order to control coronavirus disease 2019 (COVID-19) occurrences.